Implementation of Criminal Sanctions Against Perpetrators of Theft Crimes Based on Legal Certainty (Case Study of Decision Number 144/Pid.B/2024/PN.Smg - Fitriani, Riska; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The case study in this research is Decision Number 144/Pid.B/2024/PN Smg. By considering Article 362 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations, the court declares that the Defendant Rilly Pradana Purnama Putra Bin Slamet Bowo Mulyono has been proven legally and convincingly guilty of committing the crime of "Theft" as in the Single Indictment of the Public Prosecutor; imposes a sentence on the Defendant, therefore with a prison sentence of 1 (one) year and 8 (eight); Declares that the length of arrest and detention that the Defendant has served is deducted entirely from the sentence imposed. Law enforcement against crime in Indonesia, especially in criminalization, should refer to a normative approach that is punitive to criminals so that it can have a deterrent effect. Minor crimes, especially minor theft, have recently attracted public attention because their handling is considered no longer proportional to the level of seriousness of the regulated crime. The current regulation of minor crimes is assumed to be a kind of protection from disproportionate law enforcement against crimes whose losses are considered not serious. Minor crimes do not only include violations, but also include minor crimes contained in Book II of the Criminal Code consisting of minor animal abuse, minor insults, minor abuse, minor theft, minor embezzlement, minor fraud, minor vandalism, and minor receiving of goods. Understanding of Supreme Court Regulation Number 2 of 2012 needs to be accompanied by efforts to educate the public about minor crimes. This is because not all people understand the things included in minor crimes (Tipiring). The crime of theft with a relatively small value of goods can go to court because currently the Public Prosecutor (PU) charges defendants with minor theft using Article 362 of the Criminal Code and not Article 364 of the Criminal Code because the limitation of minor theft regulated in Article 364 of the Criminal Code is limited to goods or money with a value of less than Rp. 250,- (Two Hundred and Fifty Rupiah). This value is certainly no longer relevant to the current situation, because there are almost no goods with a value of less than Rp. 250,-.